Etnografi Kehidupan Pengrajin Pandai Besi di Jorong Tangah Koto Nagari Sungai Pua - Jamal Afdillah (Jurnal Nomosleca, 2024)
This research describes the life of blacksmith craftsmen in Jorong Tangah Koto, leading to a dynamic in the activities they are currently engaged in. This research uses qualitative methods, namely observation data collection techniques and in-depth interviews. Meanwhile, for the selection of informants, purposive sampling was used, namely 2 key informants, blacksmith craftsmen and ordinary informants including the nagari government, the general public and community leaders in Jorong Tangah Koto Nagari Sungai Pua.The results of ethnographic research show that the description of the life of blacksmith craftsmen in Jorong Tangah Koto leads to a dynamic in the activities they are engaged in. The decline in income occurred due to the impact of blacksmith crafts not selling well on the market.